Automated three-dimensional reflection traveltime modelling to detect dipping layer geometries from active seismic data - Matlab code - Zappalà, Samuel (Uppsala University, 2026)
The code presented in this dataset determines the best-fitting geometries (strike and dip angles) of a dipping reflector with a known surface intersection from pre-stack seismic data, using an automated approach implemented in Matlab©. The modelling is first run on a single gather and then iterated on all available gathers.
It requires as input shot or receiver gathers in SEG-Y format, along with first-break and reflection traveltime picks in ASCII format. If desired, also a migrated stacked section can be uploaded. In addition to the resulting reflector geometry the output data shows RMS error matrix, modelled pre- and post-stack reflection and azimuth coverage.
The data provide also two example cases, a 3D synthetic model and a 2D real case.
To use the code, open ReflectionModelling.m on Matlab© and modify the first part of the code with the desired input and variables, then, run the code and enjoy!
See ReflectionModelling_Manual.pdf for more details.
Automatiserad tredimensionell reflektionsresetidsmodellering för att upptäcka lutande lagers geometrier från aktiv seismisk data – Matlab-kod
Keywords: hyperbolic functions; modelling; seismic data; geological structures; Matlab; Matlab; Geophysics; Geofysik; Algorithms; Algoritmer